System of Question Sentence in Tontemboan Language - Intama Jemy Polii (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aims to describe the question system sentence of Tontemboan language based on its form, propositional function, and the meaning it refers to. This study used a qualitative method with a descriptive design. Based on the results of the research, the form of question sentences in the Tontemboan language can be classified into three types, namely (1) interrogative sentences marked by the use of interrogative words: sapa, sei, kawisya, ambisya, pira, kitu, and kensya, (2) question sentences marked by the use of interrogative intonation, and (3) interrogative sentences marked by the use of question particles re'en and wei. Based on the proposition, Indonesian language question sentences are categorized into: (1) WH-question questions, (2) yes-no questions, and (3) questions commonly called alternatives. The function of the Tontemboan language question sentence, according to the meaning, referred to varied dependence on the form of the question used, question word, intonation, and question particle.